2014
DOI: 10.1534/genetics.114.167460
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions Between Shox2 and Hox Genes During the Regional Growth and Development of the Mouse Limb

Abstract: The growth and development of the vertebrate limb relies on homeobox genes of the Hox and Shox families, with their independent mutation often giving dose-dependent effects. Here we investigate whether Shox2 and Hox genes function together during mouse limb development by modulating their relative dosage and examining the limb for nonadditive effects on growth. Using double mRNA fluorescence in situ hybridization (FISH) in single embryos, we first show that Shox2 and Hox genes have associated spatial expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…Together with the fact that the perichondrial expression of Hox13 was also proposed to pattern the autopodial skeleton (Villavicencio-Lorini et al, 2010), our study indicates that the patterning can be exerted by controlling the specification and differentiation of the perichondrial osteogenic precursor cells to simultaneously modulate the patterning of cartilaginous mode and bone formation. Interestingly, in the HoxA/D compound mutant, the expression of Shox2 in the embryonic perichondrium, but not chondrocytes, is severely affected (Neufeld et al, 2014), indicating that Shox2 itself is a key effector for Hox-TALE patterning system in the stylopod and further supports the idea that Hox-TALE patterns skeletal elements by commissioning perichondrial cells. Given the instructive role of perichondrial cells on chondrocyte differentiation and maturation (Ohbayashi et al, 2002), further dissection of Shox2-specific targets in the osteogenic lineage would further highlight key factors involved in such patterning function.…”
Section: Cell Lineages That Are Commissioned For Patterningmentioning
confidence: 58%
See 1 more Smart Citation
“…Together with the fact that the perichondrial expression of Hox13 was also proposed to pattern the autopodial skeleton (Villavicencio-Lorini et al, 2010), our study indicates that the patterning can be exerted by controlling the specification and differentiation of the perichondrial osteogenic precursor cells to simultaneously modulate the patterning of cartilaginous mode and bone formation. Interestingly, in the HoxA/D compound mutant, the expression of Shox2 in the embryonic perichondrium, but not chondrocytes, is severely affected (Neufeld et al, 2014), indicating that Shox2 itself is a key effector for Hox-TALE patterning system in the stylopod and further supports the idea that Hox-TALE patterns skeletal elements by commissioning perichondrial cells. Given the instructive role of perichondrial cells on chondrocyte differentiation and maturation (Ohbayashi et al, 2002), further dissection of Shox2-specific targets in the osteogenic lineage would further highlight key factors involved in such patterning function.…”
Section: Cell Lineages That Are Commissioned For Patterningmentioning
confidence: 58%
“…Strikingly, Shox2 mutation causes loss of the stylopod in both forelimbs and hindlimbs, which was thought to be attributed to the direct function of Shox2 in chondrogenesis (Bobick and Cobb, 2012;Yu et al, 2007). However, an epistatic additive interaction between HoxA/D genes and Shox2 was seen in limb development (Neufeld et al, 2014), suggesting an involvement of Shox2 in the Hox-TALE patterning system.…”
Section: Introductionmentioning
confidence: 99%
“…S1; Rincon-Limas et al 1999). On the other hand, some proximal gene expression, including Shox2 and Hoxa11 (Neufeld et al 2014), was clearly gained within the distal domain, suggestive of an extension of proximal identity into the most distal limb aspect ( Fig. 1B,D; Supplemental Fig.…”
Section: Genetic Identity Of Hox13 Double-mutant Limbsmentioning
confidence: 92%
“…Mice with a loss of Shox2 function exhibited severe truncation of the stylopod bone of fore‐ and hindlimbs in addition to hypoplasia of the hindlimb zeugopodal bone (Bobick & Cobb, ; Cobb et al., ). Shox2 showed overlapping expression with Hoxa9‐11 in the mesenchyme of the stylopod and zeugopod then in the outer layer of the perichondrium and proliferating chondrocytes but not in the autopod (Neufeld, Wang, & Cobb, ; Swinehart, Schlientz, Quintanilla, Mortlock, & Wellik, ). Genetic analysis revealed that Shox2 is a downstream gene of Hox11 (Gross, Krause, Wuelling, & Vortkamp, ).…”
Section: Discussionmentioning
confidence: 99%
“…SHOX2 also bind to this CHBRL (Supporting Information Figure C) indicating that SHOX2 participate self‐regulation in coordination with HOX11. Interestingly, genetic analysis also suggested that Hox and Shox2 coordinate during development of the stylopodal and zeugopodal cartilage (Neufeld et al., ). Supporting this observation, we showed that SHOX2 also shares common binding regions of some Hox target genes with HOXA11 and HOXA13 (Figures and , Supporting Information Figure and Table ).…”
Section: Discussionmentioning
confidence: 99%